Analisis Biomekanika Pada Postur dan Gerak Tubuh Operator Book Lift Guna Mengidentifikasi Risk of Musculoskeletal Disorders - Alex Alfandianto; Margaretta Hernita Erni Dwi Putri (SAINTEK : Jurnal Ilmiah Sains dan Teknologi Industri, 2017)
Manual Material Handling (MMH) is expressed as an art and science that includes handling, transfer, packing, storage and monitoring. In this study, the problems faced by the book lift operator are less attention to the risk of spinal cord injury, the operator should pay attention to the safety and health level, to know the biomechanical hazard factors, as well as the MMH activity that endanger or cause pain in the operator. The observations focused on one binder carrier operator at the APK Laboratory, which is the part that moves the book directly from the floor to the point of stomach inclination or the designated destination location with a book weight of 8 kg. The identification of this case study uses a biomechanical approach to find out the compressive forces at an inclination angle. The yield of compressive force of the inclination angle is -22572.3 N and -29972,9 N against the L5 / S1 compression reference standard, the comparative value must be below 3400 N, in order to obtain safe operator category. So the results of these comparisons have a relation or synopsis of posture and body movements of operators belonging to the category safe or not occur Risk of Musculoskeletal Disorders.